Punching Shear Resistance of Reinforced Concrete Flat Slabs Strengthened by CFRP and GFRP: A Review of Literature - Hadi Al-Maliki; Ali Al-Balhawi; Asma Ali (Engineering and Technology Journal, 2021)
Flat reinforced concrete (RC) slabs or plates are still widely used in buildings and are most popular in single or multiple story floor construction systems. This is due to the ease and speed of implementation as well as the continuous smoothness that is provided in relation to the locations of members. Flat slab systems have an inadequate shear strength in both directions. Thus, they are subjected to a shear failure at their intersections with columns, which results in the collapse of a larger part of the structure. Shear failure occurs due to many reasons including changing the functions of the facility, the technical errors in the design and implementation procedures, an increase in the load, deterioration of materials, and poor quality. The carbon fiber reinforced polymer (CFRP) sheets/strips and glass fiber reinforced concrete polymer (GFRP) are used as a composite section formulated when there is a structural deficiency. Strengthening by using CFRP and GFRP provide an improvement in the punching shear resistance in both directions as well as flexural strength, ductility, and hardness. They are more suitable for a practical use as a substitute for other costly and difficult approaches such as increase the cross-sectional area of columns and so on. This paper reviews the up to date studies of enhancing the shear resistance of flat slabs by CFRP/GFRP and discusses the used materials for strengthening flat slabs and the used methods, which are used to implement these materials. Also, a summary for the cited studies are stated and the possible future works are suggested.